A systematic review of mental health measurement scales for evaluating the effects of mental health prevention interventions. (1st April 2020) - Breedvelt, Josefien J F; Zamperoni, Victoria; South, Emily; Uphoff, Eleonora P; Gilbody, Simon; Bockting, Claudi L H; Churchill, Rachel; Kousoulis, Antonis A
Abstract: Background: Consistent and appropriate measurement is needed in order to improve understanding and evaluation of preventative interventions. This review aims to identify individual-level measurement tools used to evaluate mental health prevention interventions to inform harmonization of outcome measurement in this area. Methods: Searches were conducted in PubMed, PsychInfo, CINAHL, Cochrane and OpenGrey for studies published between 2008 and 2018 that aimed to evaluate prevention interventions for common mental health problems in adults and used at least one measurement scale (PROSPERO CRD42018095519). For each study, mental health measurement tools were identified and reviewed for reliability, validity, ease-of-use and cultural sensitivity. Results: A total of 127 studies were identified that used 65 mental health measurement tools. Most were used by a single study (57%, N = 37) and measured depression ( N = 20) or overall mental health ( N = 18). The most commonly used questionnaire (15%) was the Centre for Epidemiological Studies Depression Scale. A further 125 tools were identified which measured non-mental health-specific outcomes. Conclusions: There was little agreement in measurement tools used across mental health prevention studies, which may hinder comparison across studies. Future research on measurement properties and acceptability of measurements in applied and scientific settings could be explored. Further work on supporting researchers to decide on appropriate outcome measurement for prevention would be beneficial for the field.